3D Determination of Message Collection and Delivery Locations for UAV-Enabled Disaster Recovery Networks - Azusa Danjo; Shinsuke Hara; Takahiro Matsuda; Fumie Ono; Ryu Miura (IEEE Access)
When a large-scale disaster happens, critical infrastructure is destroyed, and many people are displaced. Unmanned aerial vehicle (UAV)-enabled disaster recovery networks can be used to support people in disaster-hit areas. However, determining UAV routes is critical to communicate with refugees. In this work, we propose a method to determine UAV locations to collect and deliver messages for UAV-enabled disaster recovery networks. Our method involves two stages: the received signal strength sensing stage and the message collection and delivery stage. We theoretically analyzed the computational complexity in terms of the number of steps and consequently evaluated the performance of our method using experimental data obtained from rural, suburban, and urban areas.